The impact of glutamine supplementation on the symptoms of ataxia-telangiectasia: a preclinical assessment - Chen, Jianmin (Mol Neurodegener, 2016)
BACKGROUND: Our previous studies of Alzheimer’s disease (AD) suggested that glutamine broadly improves cellular readiness to respond to stress and acts as a neuroprotectant both in vitro and in AD mouse models. We now expand our studies to a second neurodegenerative disease, ataxia-telangiectasia (A-T). Unlike AD, where clinically significant cognitive decline does not typically occur before age 65, A-T symptoms appear in early childhood and are caused exclusively by mutations in the ATM (A-T mutated) gene. RESULTS: Genetically ATM-deficient mice and wild type littermates were maintained with or without 4 % glutamine in their drinking water for several weeks. In ATM mutants, glutamine supplementation restored serum glutamine and glucose levels and reduced body weight loss. Lost neurophysiological function assessed through the magnitude of hippocampal long term potentiation was significantly restored. Glutamine supplemented mice also showed reduced thymus pathology and, remarkably, a full one-third extension of lifespan. In vitro assays revealed that ATM-deficient cells are more sensitive to glutamine deprivation, while supra-molar glutamine (8 mM) partially rescued the reduction of BDNF expression and HDAC4 nuclear translocation of genetically mutant Atm(−/−) neurons. Analysis of microarray data suggested that glutamine metabolism is significantly altered in human A-T brains as well. CONCLUSION: Glutamine is a powerful part of an organism’s internal environment. Changes in its concentrations can have a huge impact on the function of all organ systems, especially the brain. Glutamine supplementation thus bears consideration as a therapeutic strategy for the treatment of human A-T and perhaps other neurodegenerative diseases.